Surgical treatment of trapeziometacarpal joint osteoarthritis - TACCARDO, GIUSEPPE (Joints, 2014)
Trapeziometacarpal joint osteoarthritis is a common cause of radial-sided wrist pain that prevalently affects women. It is diagnosed on the basis of a thorough history, physical examination, and radiographic evaluation. While radiographs are used to determine the stage of disease, treatment is dependent on the severity of the symptoms. Non-surgical treatment frequently consists of activity modification, non-steroidal anti-inflammatory drugs, splinting and corticosteroid injections. After failure of conservative treatment, various surgical options exist depending on the stage of the disease. These options range from ligament reconstruction or osteotomy, for early painful laxity, to trapeziectomy, arthrodesis and arthroplasty for more severe osteoarthritis. This article reviews the literature supporting the various surgical treatment options and analyzes the surgical techniques most frequently used in the different disease stages.